2016
DOI: 10.1097/md.0000000000003958
|View full text |Cite
|
Sign up to set email alerts
|

Total time of operation is a risk factor of stroke-associated pneumonia in acute ischemic stroke patients with intra-arterial treatment

Abstract: Background and purpose:Stroke-associated pneumonia (SAP) is associated with poor functional outcome in patients with acute ischemic stroke (AIS). The objective of this study was to identify predictors of SAP in patients underwent intra-arterial treatment (IAT).Methods:Consecutive patients with AIS within 6 h from the symptom onset underwent IAT were enrolled. Independent predictors of in-hospital SAP after AIS were obtained using multivariable logistic regression. Kaplan–Meier survival curves were calculated a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 31 publications
2
7
0
Order By: Relevance
“…In accordance with previous studies, our study also found that old age [27], severe neurological deficits [27], high baseline glucose level [28], pneumonia [29,] and sICH [30] were independent predictors for poor functional outcome. Moreover, small baseline infarct core (ASPECTS 8-10) [31], successful revascularization (mTICI 2b-3) [27,32], good collateral status (2-3) [33,34], and OTT ≤6 h [27,35,36] were protective factors.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…In accordance with previous studies, our study also found that old age [27], severe neurological deficits [27], high baseline glucose level [28], pneumonia [29,] and sICH [30] were independent predictors for poor functional outcome. Moreover, small baseline infarct core (ASPECTS 8-10) [31], successful revascularization (mTICI 2b-3) [27,32], good collateral status (2-3) [33,34], and OTT ≤6 h [27,35,36] were protective factors.…”
Section: Discussionsupporting
confidence: 79%
“…In our study, all patients were managed in intensive care units after EVT in stroke centers. The previous study showed that the incidence of pneumonia was as high as 57% for patients treated in intensive care units [29]. Also, the post procedural management following EVT was critical and needed more attention in future.…”
Section: Discussionmentioning
confidence: 99%
“…Dysphagia and stroke-induced immunodeficiency were the major risk factors that predispose patients to SAP. [ 22 , 23 ] Besides, age, stroke severity, level of consciousness, chronic obstructive pulmonary disease, and coronary artery disease may be associated with SAP. [ 24 ] Furthermore, a range of research developed some predictive scores based on the risk factors to predictive SAP.…”
Section: Discussionmentioning
confidence: 99%
“…The risk of serious adverse events, particularly symptomatic intracerebral hemorrhage is also well known 8 . However, these patients are also prone to medical complications and other adverse events 9‐11 …”
Section: Introductionmentioning
confidence: 99%